Consequences of Re-Enacting GBHN (Guideline for State Policy) in National Development Indonesia - Achmad, Isyrofah Amaliyah; Sanjaya, Novianto; Achmad, Millah Aldillah (RSF Conference Series: Business, Management and Social Sciences, 2023)
The research titled "Consequences of Reimplementing the GBHN in National Development Indonesia" delves into the implications of reintroducing the GBHN (Guideline for State Policy) in the context of national development. The GBHN, a strategic policy framework about The 1945 Constitution, is the written Constitution of the Republic of Indonesia. It was previously utilized to guide Indonesia's development initiatives but was later abolished. This study aims to comprehend the potential outcomes of its reinstatement. Through a comprehensive legal analysis, the research explores the historical background, legal framework, and socio-economic impact of re-enacting the GBHN. By examining comparable case studies and conducting in-depth interviews, the study investigates the possible benefits, challenges, and transformative aspects of returning to the GBHN system. The research contributes valuable insights into the legal and developmental dimensions of policy-making, shedding light on the intricate interplay between policy formulation, governance, and national progress.